(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2025)
We present interface-resolved direct numerical simulations of decaying homogeneous isotropic turbulence laden with finite-size spherical particles. The fluid phase is solved using the lattice Boltzmann method (LBM) coupled with the interpolated bounce-back (IBB) scheme to impose no-slip boundary conditions at moving particle surfaces. The accuracy of the method is verified against benchmark cases, including the settling sphere experiment of ten Cate et al. and pseudo-spectral simulations of single-phase turbulence. Simulations are performed at an initial Taylor-scale Reynolds number in the range of Reλ=20-45 for particle volume fraction of 2.5%. The results show that finite-size particles enhance small-scale flow structures and accelerate the decay of turbulent kinetic energy compared to the single-phase case. Energy spectra analysis reveals a redistribution of energy from large to small scales. These findings provide new insights into turbulence modulation mechanisms in particle-laden flows and demonstrate the applicability of LBM for fully resolved particle–turbulence interaction studies.